Acceptance Test And Fiber Levels Of Red Bean Ice Cream As An Alternative Snack For Obesity Prevention In Adolescent - Anvy Aditya Raksesi; Ani Intiyati; Melina Sari; Mujayanto (Politeknik Kesehatan Kemenkes Surabaya, 2023)
Obesity is a pathological state. According to the 2019 AKG, adolescent fiber needs are 37 grams. If snacks are given 10% of the need, then 3.7 grams are obtained per snack. To meet this need, an innovative high-fiber snack is made by formulating red beans into ice cream. The aim is to determine the acceptability and fiber content in red bean ice cream products as an alternative snack to prevent obesity. The research method was an experiment on 4 different formulations with a ratio of skimmed milk and red beans 100 : 0 g, 50 : 50 g, 70 : 30 g , 60 : 40 g then an acceptability test was carried out. The highest acceptability test results will be tested for fiber content with the control formulation. The results showed that the formulation of red bean ice cream that had the highest acceptability was formulation 4 (EKM 4), which was 3.83 in the liking category and contained fiber content of 2.43% / 100 g. One serving of red bean ice cream based on calorie needs is 85 grams with a fiber content of 2.1 grams. Conclusion, the formulation with the highest acceptability is in formulation 4 (EKM 4).